METODOLOGI QIYAS DALAM ISTINBATHHUKUM ISLAM - Sakirman Sakirman (YUDISIA : Jurnal Pemikiran Hukum dan Hukum Islam, 2018)
Shariah is the concrete embodiment in the middle of thecommunity. Even so, the Shari'ah as puts the teachings of Islamgrew in a variety of situations, conditions and aspects of spacetime.The ontological reality of Shari'ah is then gave birth to theepistemology of Islamic law (fiqh) which is basically a remotelyand called the scholars with a social fact enclosing them. Thesehistorical facts show that Islamic law (fiqh) justification of theplurality of the formulation of the law due to the role ofepistemology "langage games" are different. Islam in the middle ofthe progress of all fields as a result of copyright, taste as well asthe work of man now this is demanded in the notice will satisfy thedevelopment of knowledge and technology. The history of thedevelopment of Islamic law have taught us that the transformationof social values, cultural, economic, and even political influencethe occurrence of changes in Islamic law.